1994
DOI: 10.1088/0953-8984/6/31/006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between arsenic precipitates and vacancy-type defects in low-temperature-grown GaAs

Abstract: We have utilized x-ray photoelectron and variable energy positron beam spectroscopies for deplh profiling excess arsenic. arsenic precipitates. and vacancy-type defects in GaAs grown by molecular beam epitaxy at low temperatures (LT-G~As). XPS results show about 1.3% excess arsenic in as-grown LT-G~As and a non-uniform depth profile of arsenic Concentration in annealed LT-G~As. Doppler broadening of the positron-electron annihilation radiation (S parameter) reveals a non-uniform depth profile of defects in ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…10 7 coincident events were recorded for each spectrum. The intensity of the annihilation with high-momentum core electrons was characterized by a W parameter calculated in the momentum range (15)(16)(17)(18)(19)(20)…”
Section: Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…10 7 coincident events were recorded for each spectrum. The intensity of the annihilation with high-momentum core electrons was characterized by a W parameter calculated in the momentum range (15)(16)(17)(18)(19)(20)…”
Section: Techniquesmentioning
confidence: 99%
“…36 Lattice relaxations were not taken into account. Theoretical W parameters are obtained from the calculated momentum distribution also in the range (15)(16)(17)(18)(19)(20)…”
Section: ϫ10mentioning
confidence: 99%
See 2 more Smart Citations
“…Positron annihilation spectroscopy has revealed that there exist a large number of monovacancies in the as-grown film but vacancy clusters in the annealed LT-GaAs. [7][8][9][10] In other words, the vacancies redistribute when annealed. On the other hand, excess As redistributes when LT-GaAs is annealed.…”
Section: ͓S0003-6951͑98͒03805-4͔mentioning
confidence: 99%